The Effect of Independent Commissioners, Audit Committee, Internal Audit, Audit Quality, Company Size on Financial Performance in Banking Companies - Navillia, Olga Cendy; Rahayu, Ruci Arizanda (Jurnal Riset Akuntansi Terpadu, 2024)
This study aims to determine the financial performance of companies in the financial sector. Financial performance is projected by Return Of Assets (ROA) as a measure of financial performance based on company operations. This study is determined by the variables of the independent board of commissioners, audit committee, internal audit, audit quality, and company size, with the object of research of banking companies listed on the Indonesia Stock Exchange for the period 2020-2022. Sampling was carried out using a purposive sampling method involving 96 sample companies. Multiple regression analysis was used as the analysis method in this study. The results showed that the independent board of commissioners, internal audit, and company size have a significant correlation with the financial performance of banking companies. Meanwhile, the audit committee and audit quality have no correlation with the financial performance of banking companies.